Nord Stream and South Stream as innovative projects, their impact on the energy sector environment and policies of the European Union - Nikitina, Ludmiła (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
Natural gas is an indispensable resource in many industries. Its share in the primary energy consumption is relatively high, both in the European Union and globally. Energy security is a priority for each country, making the diversification of suppliers, energy sources and the construction of energy transmission systems come first in its implementation of energy policy goals. The paper discusses the following issues: - the growing demand for gas in the European Union and its consumption forecasts. Energy security - diversification of gas suppliers and transmission systems. Innovative projects Severnyi Potok (Nord Stream) and Yuzhny Potok (South Stream). Political controversies and economic reality. The analysis of media rhetoric on this topic; - do Nord Stream and Yuzhny Potok (South Stream) pose a threat to the energy security of the European Union, or are they strategically important projects, ensuring the stable and secure supplies of natural gas to EU countries? Environmental protection and the Nord Stream and South Stream pipelines. Economic cooperation between European and Russian companies in the implementation of the above projects.

Gaz ziemny jest niezbędny w wielu gałęziach przemysłu. Udział gazu ziemnego w strukturze zużycia tak zwanej energii pierwotnej pozostaje na dosyć wysokim poziomie, jak w Unii Europejskiej, tak i w świecie. Każde państwo uważa swoje bezpieczeństwo energetyczne za sprawę priorytetową, a realizując założone cele w polityce energetycznej na pierwsze miejsce stawia dywersyfikację dostawców, surowców energetycznych i budowę systemów przesyłowych dla nich. W artykule poruszono następujące kwestie: - rosnące zapotrzebowanie na gaz w Unii Europejskiej i prognozy jego zużycia; bezpieczeństwo energetyczne - dywersyfikacja dostawców gazu i systemów przesyłowych; innowacyjne projekty Sewernyj Potok (Nord Stream) i Jużnyj Potok (South Stream) Potok; kontrowersje polityczne i realność ekonomiczna; analiza retoryki medialnej na dany temat; - Nord Stream i Jużnyj Potok (South Stream) stanowią zagrożenie dla bezpieczeństwa energetycznego Unii Europejskiej, bądź są strategicznie ważnymi projektami, zapewniającymi stałe i bezpieczne dostawy gazu ziemnego do państw unijnych? Ochrona środowiska i rurociągi Nord Stream i South - Stream. Współpraca gospodarcza firm europejskich i rosyjskich w realizacji powyższych projektów.
Innowacyjne projekty Nord Stream i South Stream. Ich wpływ na sektor energetyczny, środowisko naturalne i klimat polityczny Unii Europejskiej
Keywords: natural gas; Nord Stream; South Stream; Russia; European Union; innovation; environmental protection; energy security; European Union; Gaz ziemny; Rosja; Unia Europejska; innowacyjność; ekologia; bezpieczeństwo energetyczne; Unia Europejska